Usability improvement of public transit application through mental model and user journey - Komang Candra Brata; Aryo Pinandito; Nurizal Dwi Priandani; Mahardeka Tri Ananta (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Using a mobile application that is featured with local public transit information can greatly improve user action, as well as assisting travelers to have a better experience while taking public transit services. Crowd environment inside a public transit is one of the most frequent causes that lead difficulties to passengers when they engaging their mobile devices to access their apps or in some conditions. Finding crucial information such as stops points and remaining time to interchanges point when switching to another line becomes more difficult in those conditions especially for foreigners who new in a particular region. This study presents the combination of a mental model and a usability approach to construct a user journey map that led to new insights on user's experiences and challenges when utilizing their mobile local transit application. This valuable information is a part of the elicitation process to propose an alternative interaction method to enhance the usability and travel experience of the public transit app. The experimental results indicate that in contrast to the existing mobile transit app, the proposed interface with the utilization of a wearable device could considerably enhance user action when trying to reach the desired location in terms of total time and performance. It implies that the proposed solution, which works through the mental model and user journey is able to intuitively enhance the public transit app usability.